THE RELATION OF PRODUCTIVE LONGEVITY OF LITHUANIAN HEAVY DRAFT MARES WITH THE UDDER CAPACITY - Chirgin Evgeny Dmitrievich; Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Iskhan Kairat Zhalelovich; Rzabayev Tolybek Serikbayevich; Zhikishev Yerlik Kaliaskarovich (Scientific Journal of Pedagogy and Economics, 2019)
complex of ZAO Semenovsky breeding plant. In mares of the Lithuanian breed, the udder capacity was the highest among the draft horse breeds: the average udder capacity was 3.01±0.04 kg, and the maximum udder capacity was 4.75 kg of milk. The udder capacity of mares of the Lithuanian heavy draft breed varied during the day, the lactation and the ontogenesis of mares, it was determined more by genetic factors - the coefficient of heritability of this trait was 0.60. The maximum duration of economic use of the Lithuanian draft mares was 23 years, during which the maximum lifelong milk yield reached 88138 kg, and the milk yield for the highest lactation was 8576 kg of milk. It was found that the udder capacity is positively correlated with the milk yield of mares. The correlation coefficient between the udder capacity and the lifetime milk yield of mare of the Lithuanian heavy draft breed was positive and significant r = +0.67. Studies have been conducted to determine the possibility of using this indicator for the selection of animals with long-term economic use and a high lifetime milk yield. It was found that it is possible during the first lactation to select mares by the udder capacity, distinguishing by the period of economic use and high lifetime milk yield.